Da ira de Deus à defesa civil: um estudo de caso sobre o terremoto de Lisboa de 1755 - Rafael Moreira Gonçalves (2024)
It was an ordinary day, despite a religious holiday, there was nothing that could demonstrate the imminent danger and the danger that might occur. People left home, went to pray, work, live life. And then the earth shook, the sea rose, and the fire came. Lisbon was razed. Many dead, many injured and so many others fleeing the tragedy. The King did not know how to act, the Church, accused sinners and feared divine punishment. It so happens that the Lisbon Earthquake has given new meaning to disasters. Until November 1, 1755, catastrophic events were associated with punishment for the sins of humanity, indeed divine. The change occurs when, by taking over the management of Lisbon in the midst of chaos, the Marquis of Pombal pushes away theology and the organization of the territory through a sequence of logical facts. This research shows how the Lisbon earthquake in 1755 influenced current disaster management and Civil Defense, as a public policy.